2012
DOI: 10.1183/09031936.00019012
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal dysphagia is a risk factor for community-acquired pneumonia in the elderly

Abstract: The aim of this study was to explore whether oropharyngeal dysphagia is a risk factor for community-acquired pneumonia (CAP) in the elderly and to assess the physiology of deglutition of patients with pneumonia.In the case-control study, 36 elderly patients (aged o70 years) hospitalised with pneumonia were matched by age and sex with two independently living controls. All subjects were given the volume-viscosity swallow test to identify signs of oropharyngeal dysphagia. In the pathophysiological study, all cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
133
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(151 citation statements)
references
References 25 publications
12
133
1
5
Order By: Relevance
“…The median quality score of the studies was 7.44 (range [5][6][7][8][9]. The median quality score of the case-control and cross-sectional studies was 7.42, which was very similar to that of the cohort studies (7.5).…”
Section: Quality Assessmentsupporting
confidence: 55%
“…The median quality score of the studies was 7.44 (range [5][6][7][8][9]. The median quality score of the case-control and cross-sectional studies was 7.42, which was very similar to that of the cohort studies (7.5).…”
Section: Quality Assessmentsupporting
confidence: 55%
“…Oropharyngeal dysphagia (OD) is a common major complaint in daily medical practice, occurring in 20-23% of older persons who live an independent life [1,2]. This condition is considered to be an important causative factor of aspiration pneumonia [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dysphagia and swallowing dysfunction are widely accepted as risk factors for pneumonia, especially in aspiration pneumonia [16,17,20,[26][27][28]; furthermore, a number of studies have shown that regular visits to the dentist and good oropharyngeal hygiene are protective against CAP [3,21,29]. In a small, case-controlled prospective study, patients with swallowing dysfunction had increased episodes of recurrent pneumonia [11], although these results were not replicated in larger studies [9,10].…”
Section: Clinical Risk Factorsmentioning
confidence: 97%
“…Chronic respiratory diseases [23][24][25], dysphagia and poor oral hygiene [3,16,17,20,21,[26][27][28][29], stroke and associated neurological dysfunction, heart failure, and certain immune deficiency states and systemic diseases (e.g., chronic renal or liver disease) may all increase the risk of incidence CAP by twoto fourfold [3]. COPD, in particular, has been widely studied and established as an important risk factor for incident pneumonia.…”
Section: Clinical Risk Factorsmentioning
confidence: 99%